Pure-In: Exploring Customer Satisfaction Performance to Increase Repurchase Intentions - Mahmud; Putra, Febrianur Ibnu Fitroh Sukono; Rahayuningtyas, Tri Esti (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research Aim: This study analyzes the influence of trust, promotion, e-service quality, and convenience on repurchase intention, with consumer satisfaction as an intervening variable. Approach: This study uses a quantitative method with path analysis analysis techniques. Samples were taken using purposive sampling techniques of 100 consumers. Research Findings: The results of the first part of the analysis show that Trust, Promotion, E-Service Quality, and Convenience have a positive and significant effect on customer satisfaction. The second part of the study, namely Trust, Promotion, E-Service Quality, and Convenience, has a large and positive effect on repurchase intention. Consumer satisfaction has a significant and positive effect on repurchase intention. Theoretical Contribution: This article is very relevant for future research that focuses on optimizing consumer experience in e-commerce, especially in integrating psychological, technological, and marketing aspects to create consumer satisfaction and loyalty. Practical Implications: E-commerce can prioritize the factors in this study to increase consumer satisfaction and repurchase intention. Research Limitations: This study only focuses on certain variables, so future research can add external variables such as economic conditions, etc.